Pengaruh Gaya Kepemimpinan dan Budaya Kerja terhadap Motivasi Pegawai Pada PT. PLN (Persero) Berastagi - Eprima Wanti Br.Ginting (Mahesa Research Center, 2023)
The purpose of this study was to determine the effect of leadership style and work culture on employee motivation at PT. PLN (Persero) Berastagi and the population is employees at PT. PLN (Persero) Berastagi totaling 30 people. The type of research used is associative, which is research that aims to determine the effect of the independent variable on the dependent variable and how close the influence or relationship is and to determine whether there is a correlation between the two variables. The data collection technique used is library research and field research by observation. interviews, and questionnaires. The results of this study indicate that the results of the F test with a Fcount value of 44.915 are greater than Ftable which is equal to 3.34, based on these results it can be explained that leadership style and work culture simultaneously have a positive and significant effect on employee motivation at PT. PLN (Persero) Berastagi. Then based on the results of the t test, the leadership style variable with a tcount value of 4.179 is greater than the ttable of 1.701 and for the work culture variable (X2) the tcount value is 3.209 greater than the ttable of 1.701 based on these results it can be explained that leadership style and culture work partially has a positive and significant effect on employee motivation at PT.PLN (Persero) Berastagi. And the Adjusted R Square value obtained is 0.752. To see the influence of the independent variable on the dependent variable by calculating the coefficient of determination (KD) = R2 x 100%, so that KD = 75.2%. This figure shows that 75.2% of the motivational variable (dependent variable) can be explained by leadership style and work culture variables (independent variable) then the remaining 24.8% is influenced by other factors not explained in this study.